POTENSI ILMIAH DAN KOMERSIAL BEBERAPA JENIS KOLEKSI BEGONIA - Merriansyah, H.; Putri, D. M.S. (Buletin Udayana Mengabdi, 2021)
Begonia  is a plant that is unique and distinctive in its asymmetrical leaf shape. This type has a variety of uniqueness, including beautiful flowers with attractive colors. At the Bali Botanic Garden, the  Begonia  collection is the largest collection in Indonesia and a superior thematic collection. As of December 2020, the  Begonia  collection which is arranged in  Begonia  Park is 1 tribe, 1 genus, 99 species, 1.073 specimens and 328 collection numbers. This manuscript describes the  Begonia  collection as one of the thematic collections in the Bali Botanic Garden which includes development, management and selected species that have scientific and commercial potential as ornamental plants. Collecting, research and development activities have also been carried out by collecting collections through exploration, digging up potential information, selecting potential species which are then developed and cultivated for sustainable use. Keywords:  Begonia , Bali Botanic Garden,  Begonia  Garden, thematic collection